2018
DOI: 10.20448/2002.41.20.27
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Accounting Information on Stock Price Predictions Through Fluctuation of Stock Price, Evidence From Indonesia

Abstract: This article describes the results of research on the effect of accounting information on the accuracy of analyst predictions, using stock price fluctuations as a mediation variable. Accounting information uses three measurements, i.e. changes in revenue, changes in net income before extraordinary (NIBE), and changes in debt. This accounting information is combined with market information such as stock price information. A sample of 54 issuers listed on the Indonesia Stock Exchange. The sample is selected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
1
11
0
6
Order By: Relevance
“…Furthermore, in Taylor and Richardson (2012) it was found that the practice of thin capitalization tended to be used in conjunction with the practice of tax havens to maximize the chances for tax avoidance by increasing the complexity of transactions involving tax haven countries. It is also stated that changes in revenue affect the accuracy of analyst predictions (Tambun, Murwaningsari, & Mayangsari, 2018). Dyreng, Hanlon, and Maydew (2008) found that companies that carry out tax avoidance proved to have a higher level of debt compared to companies that did not do tax avoidance.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Furthermore, in Taylor and Richardson (2012) it was found that the practice of thin capitalization tended to be used in conjunction with the practice of tax havens to maximize the chances for tax avoidance by increasing the complexity of transactions involving tax haven countries. It is also stated that changes in revenue affect the accuracy of analyst predictions (Tambun, Murwaningsari, & Mayangsari, 2018). Dyreng, Hanlon, and Maydew (2008) found that companies that carry out tax avoidance proved to have a higher level of debt compared to companies that did not do tax avoidance.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Additionally, the low educational level of many construction workers is a barrier to improve safety at construction sites. Lubega et al (2000) mentioned that the cause of accident in construction site is directly related to inadequate of safety regulation, no force to use the regulation in site, no safety consideration by personnel on site, no encourage professional people to work in site, mechanical problem of construction machinery and equipment, and chemical or physical disturbance Tambun, Murwaningsari & Mayangsari (2018).…”
Section: Personal Protective Equipmentmentioning
confidence: 99%
“…Through the fair process in performance appraisal, employees can be more productive and committed to perform their tasks. Appraisal process is perceived by employees to be fair when performance evaluation is done based on standards and fair policies (Erdogan, 2002;Subair and Oriogu, 2016;Tambun et al, 2018). The performance appraisal perception of employees is reflected through their behavior at work.…”
Section: Relationship Between Performance Appraisal and Intention To mentioning
confidence: 99%